Analysis of rbcL gene sequence genetic variation in Dermatophyllum gypsophilum subsp. guadalupense NCBI Popset 2440747772 using RFLP in silico - Cici Mustika; Afifatul Achyar (Tropical Genetics, 2023)
Dermatophyllum gypsophilum subsp. guadalupense is a rare species of flowering plant in the legume family known by the common name Guadalupe Mountain necklacepod. This plant is native to New Mexico and Texas in the United States. The rbcL gene encoding the RuBisCO protein is thought to cause this gene sequence to have a low mutation rate compared to other barcode genes in cpDNA so that the level of similarity between species is quite high. This study used restriction enzyme PciI. This study aimed to analyze genetic variation in rbcL gene sequence in Dermatophyllum gypsophilum subsp. guadalupense NCBI with PopSet 2440747772 using RFLP in silico. The results of this study showed genetic variations in the rbcL gene sequence of Dermatophyllum gypsophilum subsp. guadalupense and 8 allele variations contained in 73 gene sequences using the restriction enzyme PciI.